1991
DOI: 10.1111/j.1559-1816.1991.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Temporal Comparison, Social Comparison, and Direct Appraisal in the Elderly's Self‐Evaluations of Health

Abstract: Elderly persons (n= 91) were interviewed about self‐ perceptions of physical health and the contribution of social comparison, temporal comparison, and direct appraisal to these judgments. Consistent with previous studies, self‐assessments tended to be mainly positive (67% reported their health as “good” or “excellent”), though tempered somewhat by the individual's objective physical condition (i.e., number of chronic diseases or disabilities). Independent of objective health, respondents' ratings were more ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
4
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 42 publications
3
93
4
2
Order By: Relevance
“…For example, many researchers have attempted to explore how schema-guided processing may affect perceptions of temporal change (e.g., Suls & Mullen, 1984;Suls, Marco & Tobin, 1991). While some research implies that the person's past qualities are affected by their current beliefs (e.g., Heckhausen et al, 1989;McFarland et al, 1992;Ryff, 1982), other research highlights how people's current qualities are affected by their recollections of their past qualities (e.g., Strack et al, 1985).…”
Section: Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many researchers have attempted to explore how schema-guided processing may affect perceptions of temporal change (e.g., Suls & Mullen, 1984;Suls, Marco & Tobin, 1991). While some research implies that the person's past qualities are affected by their current beliefs (e.g., Heckhausen et al, 1989;McFarland et al, 1992;Ryff, 1982), other research highlights how people's current qualities are affected by their recollections of their past qualities (e.g., Strack et al, 1985).…”
Section: Cognitionmentioning
confidence: 99%
“…They posit that this need for positive self-evaluations can prompt the individual to construct temporal comparisons that reflect positively on the self. A temporal comparison is defined as the consideration of how one's current standing on an attribute relates to one's past standing on the attribute (Albert, 1977;Levine & Moreland, 1987;Suls, Marco, & Tobin, 1991). Albert (1977) believed that temporal comparison was a corollary to social comparison theory (Festinger, 1954).…”
Section: Cognitionmentioning
confidence: 99%
“…The application of social comparison theory to the psychology of aging, however, is recent, and has been relatively limited in scope. Several researchers have examined the frequency with which elderly people report engaging in social comparison and have found that for most elderly individuals, social comparison is a naturally occurring process (Heidrich & Ryff, 1993a;Rickabaugh & Tomlinson-Keasey, 1997;Suls, Marco, & Tobin, 1991). Other studies with older women have examined social comparison as an evaluative rating, that is, self relative to others (Heidrich & Ryff, 1993a;Robinson-Whelen & Kiecolt-Glaser, 1997), or have focused on global emotional consequences of comparison (Heidricb & Ryff, 1993b).…”
Section: Ocial Comparisonmentioning
confidence: 99%
“…Persons with chronic illness often use others with similar illness as a comparison group in the appraisal process (Affleck & Tennen, 1991). The use of temporal comparison, where the individual appraises his or her health relative to a point(s) in the past, has also been observed (Suls, Marco, & Tobin, 1991), as has the use of "cognitively assembled" comparison groups (Tornblom, Stern, Pirak, Pudas, & Tornlund, 1993). Evidence also exists that different-aged persons approach the appraisal process in qualitatively distinct ways (Tornblom et al, 1993).…”
mentioning
confidence: 99%